Electroacupuncture improves depression with constipation by balancing gut microbiota in WKY rats - Li, Xiang; Li, Guancheng; Cui, Kaiyu; Yin, Xuan; Yang, Wei; Li, Wei; Xu, Shifen (Frontiers in Microbiology, 2026)
Accumulating evidence underscores the pivotal role of the gut microbiota in the pathogenesis of depression. In this study, we employed the Wistar-Kyoto (WKY) rat, a well-established animal model of depression comorbid with constipation. Using 16S rRNA gene sequencing, we characterized the gut microbial community structure and investigated the impact of microbiota modulation on depressive-like behaviors and gastrointestinal dysfunction. Comparative analyses revealed that WKY rats exhibited significantly increased relative abundances of Proteobacteria, Bacteroidetes, and Desulfobacterota, accompanied by a marked reduction in Firmicutes compared to control Wistar rats. Fecal microbiota transplantation (FMT) demonstrated that colonization of WKY rats with microbiota from Wistar rats restored microbial composition, improved depressive-like behaviors, and normalized gut motility. In contrast, Wistar rats receiving microbiota from WKY donors developed depression-like phenotypes and impaired intestinal function. Moreover, electroacupuncture (EA) treatment not only alleviated depressive-like behaviors in WKY rats but also promoted recovery of colonic epithelial ultrastructure and rebalanced gut microbial composition. Collectively, these findings demonstrate that both FMT and EA effectively ameliorate depressive behaviors and constipation in WKY rats, with EA likely exerting its therapeutic effects through modulation of the gut microbiota.